Characterization of Bi2S3 nanorods and nano-structured flowers prepared by a hydrothermal method - Phuruangrat A. (2014)
Bismuth sulfide nanorods and nano-structured flowers were synthesized by hydrothermal reaction of bismuth nitrate pentahydrate and thiourea solutions, containing 1 and 2 ml of 65% HNO3, respectively. By using X-ray diffraction (XRD), selected area electron diffraction (SAED), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and high resolution TEM (HRTEM), the products were specified as orthorhombic Bi2S3 in the shapes of nanorods and flower-like clusters of nanorods, with the growth of nanorods in the [001] direction. A diffraction pattern was also simulated, and was in good accordance with the SAED pattern obtained from the experiment. © 2009 Elsevier B.V. All rights reserved.